Motion analysis of trunk tilt and hip joint in Uchimata (inner thigh throw) - Miyazaki, S.; Nagao, H.; Inoue, K.; Haga, K.; Tsukada, M.; Itami, N.; Yamada, H.; Ogawara, K. (Association for the Scientific Studies on Judo, Kodokan, 2017)
This study aimed to compare in the anterior trunk tilt and joint angle of the hip of thrower in uchimata (inner thigh throw) between five skillful and seven clumsy or eight high and four low career judo players by using a biomechanical approach. A computerized 3D motion analyzer (MAC 3D System, Motion Analysis Corp, Santa Rosa, CA) was used for collection of kinematics data. Experimental results indicated that high career judo players controlled anterior trunk tilt by raising their head at the end phase of uchimata. To master thismotion leads to the prevention of neck trauma of judo.